خبرِواحد اور قیاس کا باہمی اختلاف : حنفی فکر کی تفہیم: The contradiction between Khabar-e-Wahid and Qiyas: An understanding of the Hanafi School of thoughts - Dr. Muhammad Suliman Asadi (DIRAYAT, 2024)
It is generally attributed to the Hanafi Aimmah that the Khabar e Wahid does not have the status in terms of authority. Although the statement among the Muhadditheen that the Khabar e Wahid is an authentic and reliable report, it should be necessary to follow it. This is the reason why in case of conflict between Khabar e Wahid and Qiyas, the Qiyas are given absolute priority by abandoning the tradition. However, the Qiyas is given absolute priority over the Khabr e Wahid, it is not a real and correct view of Hanafi Ammah, because the arguments and scholarly statements of Hanafi Aimmah are absolutely clear, and those statements describe this aspect. They are that if there is evidence of the validity of the tradition, it would be followed according to the tradition and counter-inferences will be made. Yes, of course, this aspect is because the scope and implementation of the Khabar e Wahid with the Hanafi Aimmah are different from the perspective of the Muhadditheen. So, this article highlights these details with the statements of different Hanafi Aimmah and explains the thoughts of Hanafi Aimmah in the way of contradiction between Khabr e Wahid and Qiyas.